Hyperthermic intraperitoneal chemotherapy following up-front cytoreductive surgery versus cytoreductive surgery alone for isolated synchronous colorectal peritoneal metastases: A retrospective, observational study - Qin, Xiusen; Siyad Mohamed, Mohamed; Zhang, Yuanxin; Chen, Yuefang; Wu, Zhijie; Luo, Rui; Yi, Liang; Wang, Hui; Wang, Huaiming (Frontiers in Oncology, 2022)
Background: To date, the value of hyperthermic intraperitoneal chemotherapy (HIPEC) following up-front resection for isolated synchronous colorectal peritoneal metastases seems controversial. Patients and Methods: This retrospective cohort study was conducted from September 1, 2012, to September 1, 2019, at a tertiary medical center in China. Patients with isolated synchronous colorectal peritoneal metastases were included in CRS plus HIPEC group or CRS alone group based on the treatment history. Overall survival and relapse-free survival were estimated using Cox proportional hazards regression analysis and Kaplan–Meier method. Results: 78 patients with isolated synchronous colorectal peritoneal metastases were identified among 396 patients with synchronous colorectal peritoneal metastases. 43 were in the cytoreductive surgery plus HIPEC group and 35 were in the cytoreductive surgery alone group. Among them, 61 patients had relapse-free survival data. The median peritoneal cancer index was 4 in all patients. After a median follow-up of 46.0 months, 5-year overall survival was 66.8% and the median relapse-free survival was 36.0 (95% CI, 6.8-65.1) months in the CRS plus HIPEC group. 5-year overall survival was 31.2 % and the median relapse-free survival was 12.0 (95% CI, 9.0-15.0) months in the CRS alone group. Cox regression analyses showed that HIPEC was the independent prognostic factor for overall survival (P = 0.004) and relapse-free survival (P = 0.049). Conclusion: Findings of the present study suggest that the HIPEC following up-front CRS could improve overall survival and relapse-free survival for patients with isolated synchronous colorectal peritoneal metastases.